Influence of the different pod positions and screening methods on soybean pod shattering - Krisnawati, Ayda; Soegianto, Andy; Waluyo, Budi; Muchlish Adie, Mochammad; Kuswanto, Kuswanto (Kuwait Journal of Science, 2021)
Pod shattering is one of the major soybean constraints in the soybean production centers, particularly in the tropics. The evaluation for pod shattering resistance of 16 genotypes was using detached and undetached pod methods on the three different pod positions on the stem. The field research was arranged in a randomized block design, during the dry season in Banyuwangi, Indonesia. The shattering evaluation was conducted in the laboratory using oven dry method. The evaluation methods to investigate the pod shattering resistance of each genotype consists of the detached pod (DP), undetached pod (UDP), and undetached whole-stem method (UWS). The result showed that the detached pod method (DP) resulted in a higher average pod shattering percentage (15%) than the undetached pod methods (UDP and UWS, 13% and 11%, respectively). Nevertheless, the detached pod and undetached pod methods provide a consistent result for the evaluation of pod shattering resistance. The detached pod with oven-dry method was suggested to be used for screening of pod shattering resistance due to offers the benefit of more genotypes being tested, homogeneous selection pressure and environmental condition. Pods at the upper part of the stem were more resistant to shattering than those of pods in the middle part and lower part, respectively. Based on the stepwise regression, the pod wall weight to pod weight ratio was suggested to be one of the influential factors in the pod shattering resistance. The shattering evaluation resulted in five soybean genotypes (Anj/G100H-28, Anj/G100H-44, Anj/Rjbs-304, Anj/Rjbs-30, and Detap 1) with consistent resistant to pod shattering based on the three methods, which further can be developed or to be used as donor parent in the breeding program for pod shattering resistance.